Evolution Pattern of Paddy Temperature Field in Quasi-low Temperature Storage in Flat Stores - WU Qiang; ZHU Dou-dou; XIONG Hong; DUAN Hai-jing; JIN Li-bing (Liang you shipin ke-ji)
This study investigated the spatiotemporal evolution of the temperature field of paddy in quasi- low-temperature storage in flat stores using experimental research and numerical simulation. he evolution pattern of the paddy temperature field was derived from a 14-month grain temperature experiment in quasi-low-temperature storage. A numerical model of the temperature field in quasi-low-temperature storage was developed and validated against experimental results. Finally, the temperature profile of paddy over 26 months was predicted by the proposed numerical model. The conclusion can be expressed as follows: During the 14-month experimental period，the overall average temperature of paddy remained below 17 ℃, with a maximum of 15.57 ℃ and a minimum of 11.32 ℃. The 26-month quasi-low temperature storage period in the storehouse was simulated by using the above model. The simulation results showed that the overall average temperature of paddy gradually increased but remained below 17 ℃. The monthly average maximum grain temperature occurred in September each year, with values of 14.85 ℃ and 15.34 ℃ in the first and second years, respectively. Similarly, the highest surface grain temperatures, 15.3 ℃ and 15.8 ℃, were also recorded in September. The evolutionary rule of the paddy temperature field, as elucidated in this paper, offers theoretical support for the quasi-low temperature storage of paddy in storehouses.